(untitled) (Italian Review of Legal History, 2017)
The examination of the statutes of some villages which straddle a border – that between Veneto and Trentino – who became early frontier constitutes an opportunity for a reflection on the legal experience of the pre-Alpine communities between Middle Ages and the modern age. Based on the comparison of these “charters”, result of elementary autonomy of “villas” which at those attributed a strong identity value, the paper aims to investigate whether the existence of imposed (and disputed) territorial boundaries by central governments and institutions have or less had effect on the proper law of the local communities.